Los proyectos artísticos – culturales en la conformación de grupos musicales del departamento de cultura del Gobierno Autónomo Descentralizado del cantón Paltas. Periodo 2014 – 2015 - Vivanco Andaluz, Pablo Fabrício (2015)
The artistic and cultural projects is the main idea with which part of this research work, whose main objective is to contribute to the artistic development - Cultural -musical through the formation of the vocal group - implements the Department of Culture of the Autonomous decentralized government Avocado-Catacocha Canton City, the universe was formed to investigate the director of the Department of Culture of GAD avocados and 4 administrative staff members, who were applied an interview guide; 200 people between musicians and inhabitants of the city of Catacocha, who are allocated a survey, giving a total of 205 people, the results showed that 86% of those surveyed said that the artistic-cultural development projects help and strengthening of the musical activity of the city, and 96% agree with the existence of a cluster, in the department of culture of GAD avocados; These results allowed the realization of a proposal that was shaping the vocal-instrumental culture department GAD avocados, Ecuadorian music group playing. It is concluded that the culture department officials have a vested interest in shaping the vocal-instrumental group, which represented the Decentralized Autonomous Government of the Canton Avocado - City Catacocha scheduled future events or invitations from other organizations and institutions, taking as reference Ecuadorian music, therefore recommended to the authorities, administrative department of culture and musicians, absolutely support the permanence and stability of the vocal-instrumental group, as it will allow a high degree of musical performance of our artists.